Strategi Pendidik dalam Pengenalan Zero Waste pada Anak Usia 5-6 Tahun di TK Muslimat NU Sumedangan Kecamatan Pademawu Kabupaten Pamekasan - Lily Nur Indah Sari; Danang Prastyo (JCE (Journal of Childhood Education), 2025)
The rise of waste problems in Indonesia is a real threat to the environment and the future. This study aims to find out the strategies of educators in introducing zero waste to children aged 5-6 years at Kindergarten Muslimat NU Semedangan. In the academic sphere, the concept of zero waste needs to be introduced early to form awareness and environmentally friendly habits. This study uses a descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. Data sources are in the form of school principals, teaching teachers and parents/guardians of children aged 5-6 years. The results of the research on the strategy of introducing zero waste are meaningful learning, habituation, providing facilities that support and involve children's parents. The challenges in implementing waste care are the influence of the outside environment that still does not care about waste and the lack of collaboration between schools and partnerships.